Etika Ekonomi dalam Bisnis Digital :Tantangan UMKM di Era Perdagangan Global - Matondang, Khairani Alawiyah; Diani, Salma; Simanjuntak, Mery Kristiani Susanti; Lubis, Aisyah Fadillah (Masyarakat Ekonomi Syariah Bogor, 2025)
This study discusses the challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in the era of global trade, particularly due to the dominance of social commerce platforms such as TikTok Shop, which has shifted consumer behavior toward cheap imported products that often disregard economic ethics principles, including fair wages and environmental sustainability. Using a qualitative descriptive method through literature studies from books and online journals, this research illustrates the market inequality experienced by local MSMEs in competing with imported goods. The findings indicate that digitalization, diversification, and branding based on local values are essential strategies to enhance MSMEs’ competitiveness in an ethical manner. Moreover, government support through restrictions on unethical imported products and campaigns promoting love for local products are strategic steps to strengthen MSMEs’ position in the digital market. This study concludes that collaboration among MSMEs, the government, and digital platforms is crucial to building a fair, sustainable, and ethical trade ecosystem that enhances the competitiveness of local products amid globalization.